In-depth Phylogenomic Analysis of Arbuscular Mycorrhizal Fungi Based on a Comprehensive Set of de novo Genome Assemblies - Montoliu-Nerin, Merce; Sánchez-García, Marisol; Bergin, Claudia; Kutschera, Verena Esther; Johannesson, Hanna; Bever, James D.; Rosling, Anna (Frontiers in Fungal Biology, 2021)
Morphological characters and nuclear ribosomal DNA (rDNA) phylogenies have so far been the basis of the current classifications of arbuscular mycorrhizal (AM) fungi. Improved understanding of the evolutionary history of AM fungi requires extensive ortholog sampling and analyses of genome and transcriptome data from a wide range of taxa. To circumvent the need for axenic culturing of AM fungi we gathered and combined genomic data from single nuclei to generate de novo genome assemblies covering seven families of AM fungi. We successfully sequenced the genomes of 15 AM fungal species for which genome data was not previously available. Comparative analysis of the previously published Rhizophagus irregularis DAOM197198 assembly confirm that our novel workflow generates genome assemblies suitable for phylogenomic analysis. Predicted genes of our assemblies, together with published protein sequences of AM fungi and their sister clades, were used for phylogenomic analyses. We evaluated the phylogenetic placement of Glomeromycota in relation to its sister phyla (Mucoromycota and Mortierellomycota), and found no support to reject a polytomy. Finally, we explored the phylogenetic relationships within Glomeromycota. Our results support family level classification from previous phylogenetic studies, and the polyphyly of the order Glomerales with Claroideoglomeraceae as the sister group to Glomeraceae and Diversisporales.